Helmintos de peces del Pacífico mexicano. XXIX. Descripción de dos monogéneos nuevos de la familia Capsalidae Baird, 1853, subfamilia Benedeniinae Johnston, 1931, de Baja California - Bravo-Hollis, Margarita (1970)
Two new monogenea of the family Capsalidae Baird. 1853, subfamily Benedeniinae Johnston, 1931, are described from fishes taken in Baja California. The first, Neobenedenia pacifica sp. n., comes from the gills of Mugil cephalus L., from La Paz; it is considered a new species because of the sagittate form of the first pair of humuli of the opisthohaptor. The second, N. longiprostata sp. n., from the gills of an undetermined serranid from Isla Rasa, differs from all known species in the extremely lengthened prostate ducts, which follow along the primary, secondary, and tertiary caecal arms and reach the caudal end of the body.